Analisis Kemampuan Pemecahan Masalah Matematika Pada Materi Pola Bilangan Ditinjau Dari Gaya Kognitif Konseptual Tempo - Hairani, Hairani; Prayitno, Sudi; Turmuzi, Muhammad; Soepriyanto, Harry (Media Pendidikan Matematika, 2023)
The purpose of this study was to describe the ability of mathematical problem solving on number pattern subjects in terms of the conceptual tempo and cognitive style of class VIII students of SMP Negeri 11 Mataram. The type of research is descriptive-qualitative. The instruments used are the Matching Familiar Figure Test, the math problem-solving ability test, and interview guidelines. Data collection methods include cognitive style tests, math problem-solving ability tests, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. Indicators of Krulik and Rudnick problem-solving stages are reading and thinking, exploring and planning, selecting a strategy, finding answers, reflecting, and developing. The results showed that students with fast, accurate, and reflective cognitive styles were able to fulfill five indicators of the Krulik and Rudnick problem-solving stages. Reflective students allocate time appropriately and thoroughly in solving problems compared to fast-accurate students, so that the answers given by reflective students are more accurate than those given by fast-accurate students. Students with an impulsive cognitive style are able to run four indicators, while slow inaccurate students are able to run three indicators of Krulik and Rudnick. Slowly inaccurate students take a long time and are less thorough than impulsive students, so the answers given by slow inaccurate students are less accurate than those given by impulsive students.